OP0301 Outcomes of Patients with Rheumatoid Arthritis and Comorbid Hyperlipidaemia. (23rd January 2014) - Rosenblatt, L.; Curtis, J. R.; Yang, A.; Hebden, T.
Abstract : Background: Patients (pts) with RA have an increased prevalence of cardiovascular disease (CVD). Whether due to disease-related factors or in part related to RA medications, many pts with RA have hyperlipidaemia, a risk factor for CVD. However, the prevalence of hyperlipidaemia in the RA population and the extent to which hyperlipidaemia impacts the risk of CVD in pts with RA has not been well characterised. Objectives: To determine, using data from a real-world setting, the overall and sex-specific risk of CV events in pts with RA, with or without comorbid hyperlipidaemia, relative to those in a non-RA cohort. Methods: This retrospective, cohort study using claims data from a US commercial health plan (2005–Q1 2011) included pts with ≥2 physician diagnoses of RA (ICD-9 714.0, 714.2) and a non-RA cohort, matched 3:1 with the RA cohort on demographics (age, gender, region, index year). Pts with only one RA diagnosis in the 12-month, pre-index ("baseline") period were excluded. Follow up began at the index date, 1 year after initation of full coverage with medical and pharmacy benefits, and lasted until the first CV event, end of enrolment, or end of data availability. Incidence of the first hospitalised CV event (composite of myocardial infarction, ischaemic stroke, percutaneous coronary intervention /coronary artery bypass graft) in the post-index period was determined for each cohort and stratified by age, sex and the presence of hyperlipidaemia (defined by the presence of a ICD-9 272.xx diagnosis claim or antihyperlipidaemic agent drug claim during the pre-index period). Cox proportional-hazards regression determined the hazard ratio (HR) for CV events, using the presence of RA as the independent variable, controlling for other baseline covariates (age, sex, hyperlipidaemia, diabetes, hypertension). Results: The RA cohort consisted of 51, 130 pts and was matched with 154, 292 non-RA pts (35.1% and 36.0% with hyperlipidaemia during baseline, respectively). The incidence of CV events per 1, 000 person-years was 5.55 for the RA cohort and 3.56 for the non-RA cohort (crude risk ratio [RR]=1.56). Within the RA cohort, incidence was 8.28 for pts with hyperlipidaemia and 3.88 for pts without hyperlipidaemia (crude RR=2.13); in the non-RA cohort, incidence was 5.78 and 2.15 for those with and without hyperlipidaemia, respectively (crude RR=2.69). When controlling for covariates, the HR of CV events for pts with RA was 1.67 (95% CI: 1.50, 1.86) relative to non-RA pts. Among covariates, presence of hyperlipidaemia conferred a significant risk of CV events (p<0.0001); no significant interaction between RA and hyperlipidaemia was found (p=0.10). Sex-specific RRs and risk differences are shown. Conclusions: This real-world analysis demonstrates that pts with RA have an increased risk of CV events and, as seen with the non-RA cohort, CV event rates are incrementally higher for those pts with hyperlipidaemia. Therefore, mitigating the increased CV risk associated with hyperlipidaemia and optimising lipid levels are key treatment strategies for pts with RA. Disclosure of Interest: L. Rosenblatt Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, J. Curtis Grant/research support from: Roche/Genentech, UCB, Centocor, CORRONA, Amgen, Pfizer, Bristol-Myers Squibb, Crescendo, Abbott, Consultant for: Roche/Genentech, UCB, Centocor, CORRONA, Amgen, Pfizer, Bristol-Myers Squibb, Crescendo, Abbott, A. Yang Employee of: Bristol-Myers Squibb, T. Hebden Employee of: Bristol-Myers Squibb